13-valent Pneumococcal Conjugate Vaccine and Haemophilus Influenzae-Tetanus Toxoid Conjugate Vaccine in Patient with Systemic Juvenile Idiopathic Arthritis Receiving Tocilizumab: Clinical Case - Ekaterina I. Alekseeva; Dar’ya D. Van’kova; Tatyana M. Dvoryakovskaya; Kseniya B. Isaeva; Rina V. Denisova; Anna V. Mamutova; Aleksandra M. Chomahidze; Nikolay A. Mayanskiy; Natalya E. Tkachenko; Maria V. Kurdup; Tatyana V. Radygina; Irina V. Zubkova (Вопросы современной педиатрии)
Background. Vaccination coverage in patients with rheumatic diseases remains extremely low. Moreover, infections are the leading cause of death in such patients. Respiratory infections mortality is 2–5 times higher in adults with rheumatoid arthritis than in overall population. The most frequent infectious complications in patients receiving Tocilizumab (first-line drug for treatment of patients with systemic juvenile idiopathic arthritis (SJIA)) are pneumonia and acute sinusitis. Their clinical course differs: slight clinical presentation, reference ranges of laboratory tests of disease activity (ESR, C-reactive protein), significant changes in lungs and paranasal sinuses according to the computer tomography. Infectious complications development can cause aggravation of prior disease itself or due to temporary immunosuppressive therapy cessation. Clinical Case Description. The experience of immunization with 13-valent pneumococcal conjugate vaccine (PCV13) and haemophilus influenzae-tetanus toxoid conjugate vaccine in the 1,5 years old boy with SJIA receiving interleukin-6 receptor monoclonal antibody Tocilizumab is presented. The result of such vaccination was increase of pneumococcal and haemophilus influenzae antibodies levels by more than two times. Meanwhile vaccination had no negative impact on the prior disease course: the levels of predictors of prior disease aggravation such as protein S100 and highly sensitive C-reactive protein did not increase significantly in comparison with the period before vaccination. Conclusion. The efficiency and safety of immunization with PCV13 and haemophilus influenzae-tetanus toxoid conjugate vaccine in the child with SJIA receiving Tocilizumab is presented.